Predictors of psychological distress during self‐isolation. (20th October 2022) - Kent, Jessica N.; Kilby, Christopher J.
Abstract: Objectives: Global pandemics, such as the current COVID‐19 pandemic, are predicted to increase in prevalence in the future. Transmission suppression techniques such as social distancing and stay‐at‐home restrictions have introduced an abundance of additional stressors while simultaneously reducing our capacity to cope with stress, thus increasing the collective burden of the pandemic. Numerous psychosocial factors have been identified to protect against distress in difficult circumstances. However, it is unknown whether these factors will continue to be protective in the pandemic context. Design: The aim of the current study was to determine whether locus of control (LOC), coping style or self‐compassion were debilitating or protective factors towards psychological well‐being (depression, anxiety, stress and positive and negative affect) during the COVID‐19 pandemic. Methods: In the current study, Australian adults ( N  = 176) completed a longitudinal online survey (two time points, 2 weeks apart) incorporating measures of demographics, locus of control, coping, self‐compassion (measured at T1), depression, anxiety, stress and positive and negative affect (measured at T1 and T2) throughout June–August 2020, during the height of lockdown in Australia. Results: Multiple regression analyses suggested that avoidant coping was predictive of increases in stress and negative affect across time points. Additionally, self‐compassion was predictive of increased positive affect across time points. Conclusions: These results suggest that the pandemic context represents a unique stressor, demanding a distinctive set of strategies and psychosocial characteristics to cope. Interventions targeted at reducing avoidant coping behaviours and promoting self‐compassion may contribute to improvements in psychological well‐being during the COVID‐19 pandemic as well as future pandemics.